1999
DOI: 10.1021/es990058h
|View full text |Cite
|
Sign up to set email alerts
|

High Plant Uptake of Radiocesium from Organic Soils Due to Cs Mobility and Low Soil K Content

Abstract: Post-Chernobyl experience has demonstrated that persistently high plant transfer of 137 Cs occurs from organic soils in upland and seminatural ecosystems. The soil properties influencing this transfer have been known for some time but have not been quantified. A pot experiment was conducted using 23 soils collected from selected areas of Great Britain, which were spiked with 134 Cs, and Agrostis capillaris grown for 19-45 days. The plant-tosoil 134 Cs concentration ratio (CR) varied from 0.06 to 44; log CR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 21 publications
3
48
0
Order By: Relevance
“…Fesenko et al (2007) positively reported lime application. Plant uptake of Cs is rather high in organic soils (Sanchez et al 1999) mainly because of low soil adsorption and higher ammonium nitrogen nutrition. In contrast, Cs uptake of rice plant was decreased by manure application (Tsumura et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Fesenko et al (2007) positively reported lime application. Plant uptake of Cs is rather high in organic soils (Sanchez et al 1999) mainly because of low soil adsorption and higher ammonium nitrogen nutrition. In contrast, Cs uptake of rice plant was decreased by manure application (Tsumura et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Calcareous soils also contain little or no Al-Si based clay material. The deficiency in K and absence of clay minerals yield conditions that enhance the uptake of 137 Cs into plants similar to that found in peat and other rich organic soils (9)(10) and on soil-to-plant uptake of 137 Cs (to be published elsewhere). The tracer distribution experiments were carried out in 250 mL Erlenmeyer flasks sitting on a rotating table.…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, we considered that potassium absorption might compete with ammonium absorption because both ions are univalent cations; hence, the soybeans may lack potassium. A lack of potassium has been found to increase cesium absorption [9,12,13]. However, the potassium concentrations in soybean did not decrease with ammonium fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the amount of radiocesium extracted by ammonium fertilizer increased the day after fertilization; therefore, soybean could absorb radiocesium. In addition, the ammonium and cesium ions are both univalent cations, and ammonium has been found to restrict cesium absorption in the hydroponics [9][10][11]. This study was used by soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation